EFFECT OF CUSTOMER RELATIONSHIP MANAGEMENT TO CUSTOMER RETENTION MEDIATED BY CUSTOMER SATISFACTION AND CUSTOMER LOYALTY - Tifliyah, Siti Zainut; Rohman, Fatchur; Noermijati, Noermijati (Universitas Brawijaya, Indonesia, 2021)
The purpose of this study was to analyze the effect of Customer Relationship Management (CRM) on customer retention mediated by customer satisfaction and customer loyalty on Priority BTN in Malang City. The population of this study is Priority BTN customers in Malang City, and the number of samples obtained is in accordance with the research criteria as many as 100 samples. The approach used in this study is a quantitative approach. The type of research based on the formulation of the problem and the purpose of the study is explanatory. The technique used in this study is probability sampling with a simple random sampling method. The research instrument used was a questionnaire analyzed using SmartPLS 3.0 software. The results showed that CRM has a direct influence on customer retention. In addition, CRM indirectly affects customer retention through mediating variable customer satisfaction and customer loyalty. The next researcher can conduct further research with broader research objects, namely at the BTN Priority bank customers nationally, and can use web-based surveys to shorten the time in researching priority customers because priority customers have high mobility.